Glycosylation in Cancer: Interplay between Multidrug Resistance and Epithelial-to-Mesenchymal Transition? - Fonseca, Leonardo Marques da; Silva, Vanessa Amil da; Freire-de-Lima, Leonardo; Previato, José Osvaldo; Mendonça-Previato, Lucia; Capella, Márcia Alves Marques (Frontiers in Oncology, 2016)
The expression of unusual glycan structures is a hallmark of cancer progression, and their functional roles in cancer biology have been extensively investigated in epithelial-mesenchymal transition (EMT) models. EMT is a physiological process involved in embryonic development and wound healing. It is characterized by loss of epithelial cell polarity and cell adhesion, permitting cell migration and thus formation of new epithelia. However, this process is unwanted when occurring outside their physiological limit, resulting in fibrosis of organs and progression of cancer and metastasis. Several studies observed that EMT is related to the acquiring of multidrug resistance phenotype (MDR), a condition in which cancer cells acquire resistance to multiple diffe¬¬¬¬¬¬rent drugs, which has virtually nothing in common. However, although some studies suggested interplay between these two apparently distinct phenomena, almost nothing is known about this possible relationship. A common pathway to them is the need for glycosylation, a posttranslational modification that can alter biological function. The present review intends to compile the main facts obtained until now in these two areas, as an effort to unravel the relationship between EMT and MDR. Keywords: multidrug resistance, epithelial to mesenchymal transition, cancer, glycosylation, ABC transporters dependent drug resistance.